Pengaruh Produk Halal dan Wisata Halal dalam Meningkatkan Pendapatan Asli Daerah di Provinsi Banten - Meri Lustianah; Dewi Rahmi Fauziah (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2022)
Banten Province is one of the provinces that has great opportunities and potential for the development of the quantity and quality of the halal industry. Apart from having many destinations that can be used as halal tourism objects, Banten also has many producers of halal goods and services. In addition, by strengthening the MSME halal industry through the use of digital technology, by increasing competitiveness. Equally important is expanding market access and facilitating access to capital as well as improving the quality of human resources (HR) based on Islamic economics and finance and increasing public literacy regarding the use of halal products in their daily lives. Based on this description, the formulation in this study is how is the effect of halal products in increasing Regional Original Income in Banten Province?; What is the influence of halal tourism in increasing Regional Original Income in Banten Province? This research method uses descriptive quantitative, where the research population is 100 people. Based on the results of the discussion on the effect of halal products in increasing local revenue in Banten Province, the t-statistic value for this hypothesis is 2.114 which is greater than 1.96, and the P-value is 0.035 or the P-value is less than 0. 05 or 5 percent. This means that there is a significant effect of strengthening halal products on increasing local revenue (PAD) in Banten Province. Furthermore, the original sample table was 0.220, meaning that the Halal Product Strengthening variable had an effect on increasing local revenue by 22%, while the remaining 78% was determined by other factors not examined in the current study. The second hypothesis, the obtained T-statistic value of 1.966 is greater than 1.96. Likewise with the P-value of 0.050, this value is still above or equal to 0.05. This means that the variable strengthening halal tourism has an effect on increasing local revenue (PAD) in Banten Province. The magnitude of the influence is 21.8 percent, while the remaining 78.2 percent is determined by other factors not examined in the current study. The results of this study are in line with research (Rahman et al., 2021) which clearly states that the sharia tourism sector is believed to be able to improve the local community's economy.